Is an ethical firm a profitable one? - Chiew, Peishan. (2008)
With the increasing competition in the marketplace, more companies are producing controversial advertisements to persuade and manipulate consumers, regardless of existing advertising regulations. This study seeks to determine if a relationship exists between advertising ethics and financial performance, and presents survey results that ascertain the ethical inclination of local firms.